PENERAPAN PENGGUNAAN FLASH CARD BERGAMBAR DALAM MENINGKATKAN KEMAMPUAN MENULIS / WRITING BAHASA INGGRIS - Irianto, Dhaniel Prasetyo (STIKES NGUDIA HUSADA MADURA, 2024)
Writing is one of the important things in mastering skill of English. Writing is a form of communication to deliver thought to express feeling through written form. However, in reality, many students still find many difficulties in writing English. Lack of vocabulary is also one of the factors that makes students find it difficult to learn English, especially to practice writing in English. Picture flash cards are a media that teachers can use to increase student vocabulary and writing. Makes the students easier to practice their skill in writing. The media uses picture flash cards, plain cards and a piece of paper that given to each student. Picture flash cards contain for picture that related with the materials used in the training. Plain card serves to write down the vocabulary list and piece of paper is used for the students to write down their writing that based o the picture on the picture flash cards that given by facilitator.